The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1128/iai.68.6.3337-3343.2000
|View full text |Cite
|
Sign up to set email alerts
|

Immune Response to an 18-Kilodalton Outer Membrane Antigen Identifies Lipoprotein 20 as a Helicobacter pylori Vaccine Candidate

Abstract: Experiments were performed using the standardized murine model of Helicobacter pylori infection to determine the immunogenicity of H. pylori outer membrane vesicles in immune protection. These vesicles, which are naturally shed from the surface of the bacterium, induce a protective response when administered intragastrically to mice in the presence of cholera holotoxin, despite the absence of the urease enzyme and associated Hsp54 chaperonin. Immunoblotting identified a specific serum immunoglobulin G (IgG) re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
82
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(85 citation statements)
references
References 66 publications
1
82
1
Order By: Relevance
“…HpaA was found to be cytoplasmic and inner membrane situated, whereas Lpp20 was isolated from both the inner and the outer membrane fractions of H. pylori cells [25,40]. Further systematic examination, conducted by different methods, contradicted previous results and revealed that HpaA is a flagellar sheath protein and Lpp 20 is an outer membrane antigen released from cells inside membrane vesicles [17,21]. Thus, it is likely that the methodology used for E. coli cell fractionation is not reliable when employed for H. pylori.…”
Section: Discussioncontrasting
confidence: 41%
See 1 more Smart Citation
“…HpaA was found to be cytoplasmic and inner membrane situated, whereas Lpp20 was isolated from both the inner and the outer membrane fractions of H. pylori cells [25,40]. Further systematic examination, conducted by different methods, contradicted previous results and revealed that HpaA is a flagellar sheath protein and Lpp 20 is an outer membrane antigen released from cells inside membrane vesicles [17,21]. Thus, it is likely that the methodology used for E. coli cell fractionation is not reliable when employed for H. pylori.…”
Section: Discussioncontrasting
confidence: 41%
“…On the other hand, the HpaA homologue (HP0410 gene product) was selected as seroreactive [5]. Moreover, both proteins (HP0410 and Lpp20) have an immunoprotective effect [21,45].…”
Section: Discussionmentioning
confidence: 99%
“…Although some bacterial factors such as the heat shock protein, H. pylori adhesin (HpaA), and flagella have also been identified as pathogenic determinants, understanding the function of H. pylori cellular components in the pathogenesis of gastric disorders requires further investigation (Park et al 2006). In addition, a few unidentified antigenic bands such as 18, 39.5, 33, and 34 kDa have been reported to be of good diagnostic value (Andersen and Espersen 1992;Galmiche et al 2000;Keenan et al 2000). For instance, Lin et al (2007) detected seven proteins in duodenal ulcer and gastric cancer serum samples with relative molecular masses of 53 kDa (flagellin A), 53 kDa (flagellin B), 67 kDa (molecular chaperone DnaK), 61 kDa (urease β subunit), 74 kDa (flagellar hook-associated protein (FliD)), 76 kDa (flagellar hook protein), and 51 kDa (serine protease (HtrA)) (Lin et al 2007).…”
Section: Virulence Factorsmentioning
confidence: 99%
“…Longitudinal sections, stained with a modified MayGrunwald Giemsa stain, were scanned by full length under light microscopy. Mice were considered protected or not according to the previously report [17] .…”
Section: Prophylactic Immunizationmentioning
confidence: 99%
“…H.pylori M r 26000 outer membrane proteinspecific antibody was produced following subcutaneous immunization of the New Zealand rabbits, while age-matched control rabbits were immunized with PBS as described previously [17] . Serum antibody specificity was determined by ELISA or immunoblotting following electrophoretic transfer of SDS-PAGE-separated (150g·L -1 acrylamide) H. pylori M r 26000 outer membrane protein to 0.45µm pore size PVDF membrane.…”
Section: Immunoblotting Analysismentioning
confidence: 99%